A Sound Therapy-Based Intervention to Expand the Auditory Dynamic Range for Loudness among Persons with Sensorineural Hearing Losses: Case Evidence Showcasing Treatment Efficacy - Formby, Craig; Sherlock, LaGuinn P.; Hawley, Monica L.; Gold, Susan L. (Seminars in Hearing, 2017)
Case evidence is presented that highlights the clinical relevance and significance of a novel sound therapy-based treatment. This intervention has been shown to be efficacious in a randomized controlled trial for promoting expansion of the dynamic range for loudness and increased sound tolerance among persons with sensorineural hearing losses. Prior to treatment, these individuals were unable to use aided sound effectively because of their limited dynamic ranges. These promising treatment effects are shown in this article to be functionally significant, giving rise to improved speech understanding and enhanced hearing aid benefit and satisfaction, and, in turn, to enhanced quality of life posttreatment. These posttreatment sound therapy effects also are shown to be sustained, in whole or part, with aided environmental sound and to be dependent on specialized counseling to maximize treatment benefit. Importantly, the treatment appears to be efficacious for hearing-impaired persons with primary hyperacusis (i.e., abnormally reduced loudness discomfort levels [LDLs]) and for persons with loudness recruitment (i.e., LDLs within the typical range), which suggests the intervention should generalize across most individuals with reduced dynamic ranges owing to sensorineural hearing loss. An exception presented in this article is for a person describing the perceptual experience of pronounced loudness adaptation, which apparently rendered the sound therapy inaudible and ineffectual for this individual. Ultimately, these case examples showcase the enormous potential of a surprisingly simple sound therapy intervention, which has utility for virtually all audiologists to master and empower the adaptive plasticity of the auditory system to achieve remarkable treatment benefits for large numbers of individuals with sensorineural hearing losses.
Keywords: Adaptive plasticity; sound therapy; dynamic range expansion; hearing aid benefit; hyperacusis; loudness recruitment; sensorineural hearing loss; sound tolerance.